Comparação entre dois sistemas hidráulicos de medição de água de irrigação de arroz - Luz, Glauco de Oliveira da (2011)
The irrigated farm crops are the main users of water. With this, in places where there is a water shortage to attend all sorts of use, this kind of activity is characterized like as a potentially conflicting, once that to produce one hectare of rice, are necessary thousands cubic meters of water. To work out this conflict, many actions are been developed, as giving rights and tax to use water. Although, to the effectiveness of that actions, is necessary an effective inspection over all of the producers and users, monitoring each volume used. Being a inspection this kind unsustainable to the manager, is necessary the study of methodologies to determine water flow and volumes of irrigation, which shall be easily understood and applied, to be used by the producers themselves. Were tested, comparatively, two sorts of hydraulics systems, sharp crested Weirs and Velocimetric Hydrometers, measurers of water flow and volumes respectively, for monitoring the volumes of irrigation of two parcels of irrigated rice in the harvest 2009/2010, located in Cachoeira do Sul city, in Capané locality. In each parcel, one with Direct tillage and area of 0,66 ha and another one with Conventional tillage and area of 0,80 ha, the monitoring of water occurred simultaneously by using the Weirs and Hydrometers installed in sequence and confined, in other words, the monitored water was the same in both systems. Was used Pluviometer to monitoring the total volume of rain fall, in order that, with the irrigation volume was calculated the total volume necessary to that rice parcels. The results of the comparative monitoring between Weirs of Thin Wall and Velocimetric Hydrometers showed a small difference in the final results, been the difference of 1,15% bigger by the Hydrometer in relation to Weir in the parcel with Direct tillage and 6,75% smaller by Hydrometer in relation to Weir in Conventional tillage. However, Were verified daily variations between the Weirs and Hydrometers that reached 82% in the Direct tillage and 39% in the Conventional tillage. The total volume monitored to each parcel was 8565,15 m³/ha in the parcel with Direct tillage and 9987,25 m³/ha in the conventional tillage, both considering the results of Weirs. With the results found and the characteristics of operation and maintenance of the analyzed systems, is checked the availability of using sharp crested Weirs for monitoring water quantity in rice crops, although by the comparatively study oh both systems, is not recommended to use hydrometers in these ways.